Energy restriction and impact on indirect calorimetry and oxidative stress in cardiac tissue in rat - Kawahara, Elisa Ito [UNESP]; Maués, Nadine Helena Pelegrino Bastos [UNESP]; dos Santos, Klinsmann Carolo [UNESP]; Barbanera, Pedro Octávio [UNESP]; Braga, Camila Pereira [UNESP]; Fernandes, Ana Angélica Henrique [UNESP] (My University, 2014)
Caloric restriction, defined as a reduction in calorie intake below ad libitum, without malnutrition can have beneficial effects. In this study, we evaluated the impact of caloric restriction of 30 and 60% on calorimetric parameters and oxidative stress in cardiac tissue in rats. Rats were randomly divided into 3 groups (n = 8): G1 = control; G2 = rats exposed to dietary restriction of 30%; and G3 = rats exposed to dietary restriction of 60%. Energy restriction decreased final body weight, oxidation of carbohydrates and lipid, oxygen consumption (VO2), carbon dioxide production (VCO2), resting metabolic rate (RMR), but elevated respiratory quotient (RQ). G3 animals also displayed an imbalance in the oxidant/antioxidant system, as revealed by the decrease in the lipid hydroperoxide (LH) level and GSH-Px activity in heart tissue. In conclusion, dietary restriction decreased oxidative metabolism, as seen by the colorimetric profiles and controlled oxidative stress in cardiac tissue.
Keywords: Calorimetry; Energy restriction; Myocardium; Nutritional parameters; Oxidative stress